Rough and tumble : aggression, hunting, and human evolution - Pickering, Travis Rayne (University of California Press, 2013)
Travis Rayne Pickering argues that the advent of ambush hunting approximately two million years ago marked a milestone in human evolution, one that established the social dynamic that allowed our ancestors to expand their range and diet. He challenges the traditional link between aggression and human predation, however, claiming that while aggressive attack is a perfectly efficient way for our chimpanzee cousins to kill prey, it was a hopeless tactic for early human hunters, who-in comparison to their large, potentially dangerous prey-were small, weak, and slow-footed. Technology that evolved.